Modern architecture in the shade of modernism (Bulletin KNOB, 2008)
E. van Houten, chief building inspector with the Municipal Housing Inspectorate during the twenties and thirties of the last century became famous in Amsterdam by the so-called Van Houten premises. At that time a lot of buildings were demolished that did not comply with the requirements of the Housing Act of 1901. These were nearly always simple middle-class dwellings from the seventeenth and eighteenth century that had been divided into a number of smaller units at the end of the nineteenth century. Bad maintenance and very intensive occupancy dealt the death blow to such old buildings. The demolition of this heritage was regretted by many. Thus the practice arose to replace historical sandstone tops on new construction, so that at least some of the original townscape was saved. Van Houten played an essential role in this.This practice was also criticized. Prominent modern architects considered the new construction with historical tops a fundamentally incorrect solution. In the meantime, in the year 2008, our approach to historicizing new construction is more subtle. In a lot of new residential districts buildings of a traditional character are being erected. This sheds another light on the architectural history of the twentieth century. In retrospect the Van Houten premises may have been less foolish than modernist architects thought. They fitted in well with the image of the historical Amsterdam city centre, and this image is now appreciated everywhere. The question arises whether the modernists were actually right. For decades architectural historians let themselves be guided without question by professional literature that in a theoretical respect completely followed a modernist pattern. It would be interesting to go through the points of the history of architecture in the Netherlands during the twentieth century once again.